Baseline brain and behavioral factors distinguish adolescent substance initiators and non-initiators at follow-up - McQuaid, Goldie A.; Darcey, Valerie L.; Patterson, Amanda E.; Rose, Emma Jane; VanMeter, Ashley S.; Fishbein, Diana H. (Frontiers in Psychiatry, 2022)
Background: Earlier substance use (SU) initiation is associated with greater risk for the development of SU disorders (SUDs), while delays in SU initiation are associated with a diminished risk for SUDs. Thus, identifying brain and behavioral factors that are markers of enhanced risk for earlier SU has major public health import. Heightened reward-sensitivity and risk-taking are two factors that confer risk for earlier SU. Methods: We characterized neural and behavioral factors associated with reward-sensitivity and risk-taking in substance-naïve adolescents (N=70; 11.1-14.0 years), examining whether these factors differed as a function of subsequent SU initiation at 18- and 36-months follow-up. Adolescents completed a reward-related decision-making task while undergoing functional MRI. Measures of reward sensitivity (Behavioral Inhibition System-Behavioral Approach System; BIS-BAS), impulsive decision-making (delay discounting task), and SUD risk (Drug Use Screening Inventory, Revised (DUSI-R)) were collected. These metrics were compared for youth who did (Substance Initiators (SI); n=27) and did not (Substance Non-initiators (SN); n=43) initiate SU at follow-up. Results: While SI and SN youth showed similar task-based risk-taking behavior, SI youth showed more variable patterns of activation in left insular cortex during high-risk selections, and left anterior cingulate cortex in response to rewarded outcomes. Groups displayed similar discounting behavior. SI participants scored higher on the DUSI-R and the BAS sub-scale. Conclusion: Activation patterns in the insula and anterior cingulate cortex may serve as a biomarker for earlier SU initiation. Importantly, these brain regions are implicated in the development and experience of SUDs, suggesting differences in these regions prior to substance exposure.